Impact of Landfill Leachate on Water Quality in Langkawi Island Using Management of Environmental System - Shamshiry, Elmira; Nadi, Behzad; Bin Mokhtar, Mazlin; Komoo, Ibrahim; Saadiah Hashim, Halimaton; Yahaya, Nadzri (Asian Journal of Chemistry, 2011)
Inefficient and/or insufficient solid waste management are one of the principal factors related to the quality degradation of natural environment. This study was conducted at Langkawi Island, which is one of the densely-populated and quite rapidly-growing touristic islands in Malaysia. The study was carried out to understand state of concepts and solid waste management practices in the island as well as their impacts on the local community, problems associated with the waste management practices, landfill leachate affecting water quality of Langkawi geopark. Environmental management system is explored by questionnaire directed towards the island residents and by interviews with personnel of Majlis Perbandaran Langkawi (municipality), key stakeholders in Langkawi Development Authority and Majlis Daerah Langkawi. The aim of this research is to evaluate the effect of landfill leachate in study area based on assessment of the criteria related to economical, social-cultural environment, physical environment and biological environment and survey on water pollution due to landfill leachate and to present some perception and views of local residents on issues related to solid waste management like the aesthetic value of the island environment.